PENGARUH LINGKUNGAN SOSIAL DAN SELF-EFFICACY TERHADAP MINAT MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PADA SISWA KELAS XII PROGRAM KEAHLIAN AKUNTANSI DAN KEUANGAN LEMBAGA SMK NEGERI DI SUKOHARJO - Mawar Nanda Utami; Asri Diah Susanti (Jurnal Pengembangan Pendidikan Akuntansi dan Keuangan (JPPAK), 2025)
This study aims to determine (1) the influence of the social environment on the interest in continuing education to college; (2) the influence of self-efficacy on the interest in continuing education to college; (3) the influence of the social environment and self-efficacy on the interest in continuing education to col lege. This type of research is descriptive quantitative research. The population in this study were grade XII students of the accounting and finance expertise program at SMK Negeri in Sukoharjo in the 2026/2027 academic year. Sampling used a proportional random sampling technique with a total of 140 respondents. The results of the study show: (1) there is a significant influence of the social environment on the interest in continuing The results of the study show that (1) there is a significant influence of the social environment on the interest in continuing education to college with a significance value of 0.000 <0.05. (2) there is a significant influence of self-efficacy on the interest in continuing education to college with a significance value of 0.000 <0.05. (3) There is a significant joint influence between the social environment and self-efficacy on the interest in continuing education to higher education with a significance value of 0.000 < 0.05.Keywords: Interest in Continuing Education; Self-Efficacy; Social Environment; Vocational High School Students